THE RESULTS OF THE STUDY OF TOPOGRAPHIC ANATOMY OF THYROID AND PARATHYROID GLANDS OF RAT - A. V. Ayusheeva (Scientific Сentre for Family Health and Human Reproduction Problems, 2014)
In this study we investigated the anatomy of thyroid and parathyroid glands of female Wistar rats line. Thyroid gland consists of two lateral lobes, the right and left, and the isthmus. Each lobe has cranial and caudal poles. Cranial poles of the lateral lobes of thyroid gland reach the height of the cricoid cartilage or the caudal edge of thyroid cartilage plates. Caudal poles of the lateral lobes of the thyroid gland come down below the isthmus and reach the level of 4-5th tracheal rings. The isthmus joins both thyroid lobes and is in front of the trachea (on the level from the 1st to the 3rd or from the 2nd to the 4th tracheal cartilages). Parathyroid glands are pair rounded organs, up to 1-1,2 mm in diameter, yellow-cream and are placed in the upper third of both lobes of the thyroid gland on laterocranial surfaces. The blood supply comes from the cranial thyroid artery and at the localization in the middle third of thyroid gland lobes - partially from caudal thyroid artery. Venous drainage is carried out in the veins corresponding to the arteries. The correlation between the age of the animal with the anatomical structure of the parathyroid glands was revealed: with increasing age of the animal connective tissue capsule becomes severe, the parathyroid gland is differentiated from the tissues of the thyroid gland and rises above its surface. From the point of view of experimental modeling of abnormalities of the thyroid and parathyroid glands it is necessary to take into account the identified feature and to use the animals of least 10 months to study the pathogenic mechanisms of organ failure formation and to search new methods of correction.